The Differences of Population Density and Morphometrics Character of Berungan (Telescopium telescopium) from Two Mangrove Area (Leachate Runoff and Charcoal Furnace Area) in Batam City, Indonesia - Yarsi Efendi; Ramses Ramses (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
The Research have done in mangrove area Telaga Punggur N :1 ° 2'39.33, E ;104 ° 7'8.83, had located near from the domestic waste dumpsite and processing (TPA) of Batam City and Sungai Bongkok Tanjung Piayu distric of Batam City, Indonesia, N; 1° 1'48.71, E; 104° 5'4.86 that used as comparison habitat. This research started from September to November 2015, have purpose to compare the population density and the difference of morphometrics of T. telescopium at two different observation sites. The sampling point determined by method of random sampling. The sample has taken by plot measurement 10x10 m and the sub plot measurement 1x1 m placed in 5 pieces plot measurement 10x10 m.The research show that there are differences significant in population density of T. telescopium between the rich nutrition that show on station 1 Telaga Punggur to the low nutrition in the station 2 Sungai Bongkok. Nutrition organic material that contained in the leachate originating from runoff domestic waste dumpsite and processed allegedly giving effect to the high population of T. Telescopium. Differences heavy metal content was significantly correlated with morphometric (length and diameter) of T. Telescopium. This research shows the higher heavy metal content in Telaga Punggur station than into the Sungai Bongkok station, described T. telescopium size or morphometric (diameter and length) are relatively small.